Highly active La0.4Sr0.6Co0.8Fe0.2O3−δ nanocatalyst for oxygen reduction in intermediate temperature-solid oxide fuel cells - Chanquia, Corina Mercedes (2014)
Pure-phase La0.4Sr0.6Co0.8Fe0.2O3−δ (LSCF) nanocrystallites were successfully synthesized by the combustion method, by employing glycine as fuel and complexing agent, and ammonium nitrate as combustion trigger. The morphological and structural characterization of the LSCF nanopowders was performed by using X-ray diffraction, N2 physisorption and electron microscopy. The LSCF nanopowder consists of interconnected nanocrystallites (∼45 nm) forming a sponge-like structure with meso and macropores, being its specific surface area around 10 m2 g−1. Crystalline structural analyses show that the LSCF nanopowder presents cubic symmetry in the Pm-3m space group. By employing the spin coating technique and different thermal treatments, symmetrical cells with different electrode crystallite size (45 and 685 nm) were built, by using La0.8Sr0.2Ga0.8Mg0.2O3−δ as electrolyte. Electrochemical impedance spectroscopy measurements were performed varying temperature and pO2. The area specific resistance of the nanostructured sample (45 nm) decreases by two orders of magnitude with respect to the submicrostructured sample (685 nm), reaching values as low as 0.8 Ω cm2 at 450 °C. This improvement is attributed to the cathode morphology optimization in the nanoscale, i.e., enlargement of the exposed surface area and shortening of the oxygen diffusion paths, which reduce the polarization resistance associated to the surface exchange and O-ion bulk diffusion process.